Emotional Coregulation in Close Relationships. (April 2013) - Butler, Emily A.; Randall, Ashley K.
Coregulation refers to the process by which relationship partners form a dyadic emotional system involving an oscillating pattern of affective arousal and dampening that dynamically maintains an optimal emotional state. Coregulation may represent an important form of interpersonal emotion regulation, but confusion exists in the literature due to a lack of precision in the usage of the term. We propose an operational definition for coregulation as a bidirectional linkage of oscillating emotional channels between partners, which contributes to emotional stability for both partners. We propose several distinctions and raise unanswered questions that will need to be addressed in order to understand the relevance of coregulation for well-being in adulthood.